Warma: mobile application for the learning of mathematics and language in educational institutions of the quechua-speaking communities in Ayacucho - Gutiérrez Gómez, Edgar (2019)
The University of Ayacucho Federico Froebel (UDAFF) is promoting a research project that seeks to improve the teaching and learning of language and mathematics for children in early education in the Quechua-speaking population of Ayacucho, through the use of mobile technologies (cell phones and tablets). Among the expected results of this project is that children in early education will have digital educational tools (from cell phones and tablets) with content adapted to the reality of Ayacucho, and that favor the learning of language and mathematics in the mother tongue of their parents (Quechua speakers), being accessible from any Quechua-speaking community. This will also serve to reduce the weakening of the Quechua mother tongue, as well as the cultural identity of the populations of the Andean peoples.